2000
DOI: 10.4049/jimmunol.165.9.5295
|View full text |Cite
|
Sign up to set email alerts
|

Monocyte Chemotactic Protein-1 Receptor CCR2B Is a Glycoprotein That Has Tyrosine Sulfation in a Conserved Extracellular N-Terminal Region

Abstract: Monocyte chemotactic protein-1 (MCP-1) binding to its receptor, CCR2B, plays an important role in a variety of diseases involving infection, inflammation, and/or injury. In our effort to understand the molecular basis of this interaction and its biological consequences, we recognized a conserved hexad of amino acids at the N-terminal extracellular domain of several chemokine receptors, including CCR2B. Human embryonic kidney 293 cells expressing Flag-tagged CCR2B containing site-directed mutations in this regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
92
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(95 citation statements)
references
References 67 publications
2
92
1
Order By: Relevance
“…Sulfated tyrosines at the N-termini of chemokine receptors play a critical role in helping these receptors bind their natural ligands. These include CCR5, CXCR4, CCR2b, and CX3CR1 as well as Duffy antigen receptor for binding chemokines [14][15][16][17]29] . Previous work has indicated that sulfated tyrosines in the N-terminus of chemotactic C5aR help to form the docking site for C5a, but not the activation site [18] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sulfated tyrosines at the N-termini of chemokine receptors play a critical role in helping these receptors bind their natural ligands. These include CCR5, CXCR4, CCR2b, and CX3CR1 as well as Duffy antigen receptor for binding chemokines [14][15][16][17]29] . Previous work has indicated that sulfated tyrosines in the N-terminus of chemotactic C5aR help to form the docking site for C5a, but not the activation site [18] .…”
Section: Discussionmentioning
confidence: 99%
“…Posttranslational modification occurs in chemokine and chemotactic receptors, including C3aR, C5aR, CCR5, CX3CR1, and CC2b [15][16][17][18][19] . We hypothesized that tyrosine sulfation might be a universal phenomenon in other 7TMS GPCRs, such as ETRA and ETRB [38] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a HEK293 cell line transfected to express CCR2, mutation of Tyr 26 resulted in a dramatic decrease in sulfation, a 10-fold decrease in binding affinity for MCP-1 and almost complete loss of activation in response to MCP-1 (5). Because the Tyr 26 mutant had no detectable sulfation, the authors concluded that Tyr 28 on CCR2 is not sulfated.…”
Section: Dydymentioning
confidence: 99%
“…This modification is catalyzed in the Golgi apparatus by the enzymes tyrosylprotein sulfotransferases 1 and 2, which preferentially sulfate tyrosine residues located near acidic residues (4), a motif found in the N-terminal regions of most chemokine receptors (3). The chemokine receptors CCR2, CCR5, CCR8, CXCR3, CXCR4, CX 3 CR1, and Duffy antigen and receptor for chemokines (DARC) have been demonstrated to contain sulfated tyrosine residues that modulate chemokine binding (5)(6)(7)(8)(9)(10)(11). Moreover, studies using differentially sulfated N-terminal peptides from various chemokine receptors have shown that tyrosine sulfation increases the binding affinity of the receptor peptides to their cognate chemokines (12)(13)(14)(15)(16).…”
mentioning
confidence: 99%